Enhancing biogas production in anaerobic co-digestion of fresh chicken manure with corn stover at laboratory scale - Mohd Johari, S.A. (Springer Nature, 2020)
Anaerobic digestion (AD) is one of the renewable technologies and a good alternative for the management of livestock manure. The present study focuses on co-digestion of fresh chicken manure (FCM) with corn stover (CS) experiments for biogas production. The objective of this study is to evaluate the effect of corn stover in the production of biogas and methane content by co-digestion. The mixing ratios of co-digestion of FCM with CS were 1:1, 1:2, and 2:1. The total solids for co-digestion were 8 for all ratios. The results showed that the ratio of 2:1 produced the highest biogas yield (46.7 m3/ton of slurry) and 53.2 of methane purity. The pH fluctuated around a range of 5.2 to 7.9 due to different stages of anaerobic digestion as a result of microbeâs activity. Â© 2020, Springer Nature Switzerland AG.